Lack of striatal-enriched protein tyrosine phosphatase affected the serotonin system, behavior, and brain morphology in mice - Moskaliuk, Vitalii; Komleva, Polina; Khotskin, Nikita; Arefieva, Alla; Shevelev, Oleg; Korablev, Alexey; Serova, Irina; Battulin, Nariman; Kulikov, Alexander; Naumenko, Vladimir; Bazovkina, Darya; Kulikova, Elizabeth (Frontiers in Psychiatry, 2026)
IntroductionMental disorders are a severe problem of modern society. Significant in these conditions are the striatal-enriched protein tyrosine phosphatase (STEP) (Ptpn5 gene) and the serotonergic system. Nevertheless, the association between them is poorly studied. The aim of this research was to investigate the effects of Ptpn5 gene knockout on behavior and the serotonin system in mice.MethodsUtilizing the CRISPR/Cas9 system, we cleaved the PTP-domain-encoding sequence from the Ptpn5 gene of C57BL/6 mice. The resulting strain (Ptpn5 KO) demonstrated STEP protein absence and ERK1/2 hyperphosphorylation (STEP substrate) in the brain. We performed behavioral phenotyping, structural magnetic resonance imaging (MRI) and biomolecular screening of the serotonergic system.ResultsPtpn5 KO mice resembled the wild type in locomotor activity, motor function, and social behavior. They were overactive during dark hours and showed reduced anxiety-related behavior, elevated grooming activity, and an increased pre-pulse inhibition index. Mutant mice performed poorly in the water-related tests. They demonstrated higher immobility time in the forced swim test but not in the analogous dry tail suspension test, and experienced difficulty finding the platform in the Morris water maze but did not fail the novel object recognition test or the operant wall task. Therefore, the observed differences may be a reaction to environmental stress rather than depressive-like behavior or learning deficiency. The Ptpn5 KO strain had a bigger cortex and striatum but a smaller midbrain and cerebellum. Serotonin and its metabolite content was lower in the frontal cortex and higher in the midbrain of Ptpn5 KO mice. A lack of STEP elevated TPH2 protein level in the hippocampus and reduced Htr1a and Htr7 mRNA expression in the midbrain and hippocampus, respectively.DiscussionThe data obtained in this study indicate a significant role of STEP in the regulation of behavior and brain architecture, and highlight the connection between STEP and the 5-HT system.